The quantification of mountains in China Based on Geographic Information System - Jiang, Xiaobo; Ji, Wei; Zeng, Hongcheng; Chen, Leiting (Computing in science & engineering, 2016)
Two criteria are chosen to determine the boundaries of mountains in China. One is the domestic criterion (DC) in China; the other is an international criterion (IC). According to the DC, there are 4 000 265 km2 mountain areas; while according to the IC, there are 4 426 130 km2 mountain areas. The mountains are classified into six categories: C1.300～1 000 m;C2.1 000～1 500 m;C3.1 500～2 500 m;C4.2 500～3 500 m;C5.3 500～4 500 m;C6.≥4 500 m. The areas of mountains in the two criteria over 3 500 m are equal (C5 & C6). Except the area of C1 in DC is larger than international criterion (the value is 324 508 km2), the areas of C2, C3 and C4 in IC are larger than DC (the values are 2 273 km2, 336 186 km2 and 133 432 km2, separately).